Peran Fiqih Ibadah dalam Meningkatkan Ketaqwaan Siswa SMA IT Al Mawaddah Warrahmah Kolaka - Akmir Akmir; Meilani Putri; Muh. Fathir Rahman; Nur Asia Ulfa; Nur Rohmatus Tsaniyah (Pusat Riset dan Inovasi Nasional, 2025)
Fiqh of worship is a branch of science that discusses the procedures of the correct implementation of worship in accordance with Islamic teachings. This research aims to analyze the role of fiqh of worship in improving the devotion of students at SMA IT Al Mawaddah Warrahmah Kolaka. students at SMA IT Al Mawaddah Warrahmah Kolaka. The method used is descriptive qualitative with a case study approach. Data were collected through observation, interview, and document study. The results showed that fiqh worship learning has a significant effect on improving students' students' devotion, which is reflected in the improvement of the quality of worship, discipline, and positive behavior in daily life.